Compressive strength and cost-effectiveness of confined waste plastic bottle brick masonry walls - Masaba, Emmison Eric; Kyakula, Micheal; Ssenyondo, Vicent (Taylor & Francis group, 2026)
Uganda faces a substantial housing deficit, and escalating construction costs resulting from unsustainable extraction of construction materials and inadequate management of plastic and sawdust waste. This study evaluates the compressive strength and cost effectiveness of Plastic Bottle Brick (PBB) masonry walls as a potential substitute for conventional concrete block walls in Mbale City, Uganda. The work specifically addresses the limited empirical evidence concerning the behaviour of vertically oriented confined PBB units incorporating uncompressed air (EB), sawdust (SD) and pit sand (PS). Compressive strength testing showed that PS walls achieved a strength of 0.6 ± 0.02 MPa, comparable to hollow concrete block (HCB) walls (0.6 ± 0.06 MPa). SD and EB walls exhibited lower strengths of 0.3 ± 0.05 MPa and 0.3 ± 0.03 MPa, respectively, below the strength of solid concrete block (SCB) walls (0.8 ± 0.03 MPa). All PBB walls demonstrated higher failure strains (1.8–2.0%) than concrete block walls (1.0–1.2%). The cost-benefit analysis considering materials, labour, time utilisation and carbon emissions costs found that EB blocks were the most economical (USD 3.22/UGX 11,694), while SCB were the least economical (USD 7.97). PBB production was commercially feasible, with casting time only 17% slower than conventional block production.
Keywords: Waste; plastic bottle; plasticbottle brick; masonry wall; compressive strength; cost-benefit analysis